2013
DOI: 10.17221/7088-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun N-terminal kinase (JNK) suppresses porcine oocyte ageing in vitro

Abstract: ABSTRACT:Oocyte ageing is a complex of processes that occur when matured in vitro oocytes are, after reaching the metaphase II stage, exposed to further in vitro culture. Aged oocytes remaining at the metaphase II stage undergo spontaneous parthenogenetic activation, or cellular death, through apoptosis (fragmentation) or lysis. The key factor in apoptotic pathway regulation is c-Jun-N-terminal kinase (JNK), stress kinase from the mitogene-activated protein kinase (MAPK) family. To investigate the effect of JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Exposure to BPS disrupts cellular signalling in the apoptotic and survival pathways (Salvesen and Walsh 2014). Evidently, it is possible to expect the interference of BPS in signal pro-apoptotic pathways and signal cascades described also in gametes, leading to an altered cell cycle and cell death Sedmikova et al 2013). Further studies focused on the mechanism of BPS action are needed for a full understanding its negative effect on reproduction on the gamete level and cell cycle regulation.…”
Section: Biological Effects Of Bpsmentioning
confidence: 99%
“…Exposure to BPS disrupts cellular signalling in the apoptotic and survival pathways (Salvesen and Walsh 2014). Evidently, it is possible to expect the interference of BPS in signal pro-apoptotic pathways and signal cascades described also in gametes, leading to an altered cell cycle and cell death Sedmikova et al 2013). Further studies focused on the mechanism of BPS action are needed for a full understanding its negative effect on reproduction on the gamete level and cell cycle regulation.…”
Section: Biological Effects Of Bpsmentioning
confidence: 99%
“…Hiraga et al (2013) showed that increased lipid content in porcine oocytes could reduce the development rate of IVF blastocysts, which is consistent with our results. In addition, JNK inhibitor could inhibit apoptosis and DNA division of aging oocytes and increase the development rate of embryos after parthenogenetic activation (Sedmikova et al, 2013). The addition of 20‐μM JNK inhibitor (SP600125) in mouse embryonic culture medium could significantly reduce blastocyst apoptosis and increase blastocyst development rate (Li, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Beside the modulation of ROS levels, CO can modulate activity of c-jun terminal kinase (JNK), a member of the MAPK family. In somatic cells, CO decreases the activity of JNK ( Morse et al, 2003 ) while in aging of porcine oocytes, it leads to the decrease of its activity and suppression of apoptosis ( Sedmíková et al, 2013 ). Additionally, CO may suppress apoptosis through the modulation of the level of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%